Understanding Public Policy towards Improving Democracy in the Digital Era: Analysis of Democracy and Technological Impact - Zuchri Abdussamad; Juriko Abdussamad; Ani Heryani; Endang Fatmawati; Ade Iskandar (Budapest International Research and Critics University, 2022)
This study discusses the understanding of public policy efforts toward improving the quality of democracy in the digital era. We chose the design of this study as a qualitative design by relying on secondary data in the form of published journals and books, and websites that actively discuss public policy issues in the technology era as part of efforts to increase democracy. The data we collect from some sources will then be analyzed under a phenomenological approach, attempting to understand a question from several existing data. The process involves a data coding system, data interpretation, and carefully evaluating the data to understand relevant to answering the problem. Based on the data we have discussed, we conclude that the understanding of public services towards improving the quality of democracy in the digital era is a public service arranged in such a way by relying on data or electronic government, where every agency has digital services. This is done to transform government services using technology ready to serve its citizens without boundaries and time